Interannual variations of nutrient concentrations in botanical fractions from extensively managed grasslands - Ruano-Ramos, A (Animal Feed Science …, 1997)
We studied interannual variations in the concentrations of N, P, K, Ca, Mg, Na, Mn, Fe, Cu, and Zn in botanical fractions from semi-natural grassland in central-western Spain. Herbage samples were collected at the ripening stage at the end of May over a 4-year period (1987, 1988, 1989 and 1991) and classified into: grasses, legumes and forbs. There was an increase in N, P and K contents from 1987 until 1991. The interannual differences in Ca, Mn, Cu and Zn concentra- tions showed no clear trends. However, the sampling year had no significant effect on Mg and Na contents. Grasses generally exhibited significant lower nutrient contents than legumes and forbs. Forbs had N, Ca, Mg and Cu concentrations midway between those of grasses and legumes, and higher P, K, Fe and Zn contents than legumes. The P, Mg, and Na contents in the three botanical fractions were inadequate for feeding livestock. However, the K, Mn, and Fe contents in the three botanical groups and the Ca, Cu, and Zn contents in legumes and forbs were within recommended ranges for cattle. The N contents were only adequate in legumes. These and forbs appear to be most suitable for cattle feeding on account of their mineral contents
Keywords: correlation; grassland; Interannual variations; Mineral content